Social and organisational support on employee outcomes: the moderating effect of emotional intelligence - Raveentheran, Anand (2018)
Research on social and organisational support have shown that receiving such support can have positive effects on employees, such as increased health and greater ability to handle stressful situations, and is also shown to increase employee productivity and attachment to the organisation. This study sets out to investigate the relationships between social and organisational support on employee outcomes such as job satisfaction and organisational commitment, and understand the effect of emotional intelligence in moderating these relationships.